Thomas Hobbes's Conception of Peace Civil Society and International Order - Jaede, Maximilian (International Political Theory,, 2018)
"Despite recent work in the history of political thought and international relations theory depicting Hobbes either as a realist or a liberal internationalist, he was in fact neither, as Jaede's thought-provoking book shows. Hobbes's theory of peace may significantly depart from our modern international order, as he argues, but it nevertheless serves as a useful vantage point from which we can-and should-critique and re-evaluate our current condition." -Professor Theodore Christov, George Washington University, USA "In this timely volume, Jaede addresses the relationship of international and civil peace, showing that Hobbes understood their close connection. His was a realistic understanding of international relations, at odds with both modern realists' focus on war and liberal internationalists' faith in international institutions. Governments, he thought, should be prepared for war and, through good rule, simultaneously pursue peace at home. Jaede's Hobbes foresees the modern reality that international peace feeds on civil peace." -Professor Deborah Baumgold, University of Oregon, USA This book explores Hobbes's ideas about the internal pacification of states, the prospect of a peaceful international order, and the connections between civil and international peace. It questions the notion of a negative Hobbesian peace, which is based on the mere suppression of violence, and emphasises his positive vision of everlasting peace in a well-governed commonwealth. The book also highlights Hobbes's ideas about international coexistence and cooperation, which he considers integral to good government. In examining Hobbes's conception of peace, it provides a fresh perspective on his international political thought. The findings also have wider implications for the ways in which we think about Hobbes's relationship to the realist and liberal traditions of international thought, and will appeal to students and scholars of political theory and international relations. .